SOCIO-CULTURAL CHARACTERISTICS ON MALE INVOLVEMENT IN SAFE MOTHERHOOD AMONG COMMUNITIES IN KWALE AND KILIFI IN COASTAL KENYA - Ouma, George; Udu, Dr.Rahma; Karanja, Prof. Simon (Global Journal of Health Sciences, 2019)
Purpose: The main purpose of this study was to establish the effect of social cultural characteristics influencing male involvement in safe motherhood among communities of Kwale and Kilifi Counties of Coastal Kenya. Methodology: The study was descriptive cross sectional design. The study focused on women of child-bearing age 15 - 49 and men aged 15 - 54 from Kilifi and Kwale counties in 14 health facilities. Qualitative and quantitative methods of data collection were used. Interviewer-administered questionnaire were administered to women who were attending ANC. Data was also collected using semi-structured interviews with health service providers, community leaders and county directors. Focus group discussions were conducted using FGD guide with four women and men groups. Analysis was done using SPSS and NVivo softwares. Results: The findings also revealed that the role of cultural beliefs and taboos associated with male involvement in safe motherhood highly featured in all the interviews and FGDs and were highlighted by all respondents.